Religious Moderation Publications in Journals of UIN Datokarama Palu: Bibliometric Analysis - Ainul Yaqin Usman; Rifa'atul Mahmudah; Muh. Quraisy Mathar; Irvan Mulyadi (Yayasan Gema Bina Nusantara, 2026)
Studies on religious moderation in Islamic higher education institutions have demonstrated significant growth in recent years. This study employs bibliometric analysis to examine scientific publications on the topic of religious moderation in journals published by UIN Datokarama Palu between 2021 and 2025. Utilizing Publish or Perish (PoP), Mendeley, Microsoft Excel, and VOSviewer, a total of 111 scientific publication documents were analyzed. The findings reveal that the quantity of research on religious moderation has increased annually. The study further identifies a centralization of religious moderation research among a limited number of authors, and that the thematic spectrum of religious moderation studies remains considerably narrow. This study recommends that UIN Datokarama Palu actively promote a publication policy on religious moderation and foster research collaboration, in order to enhance the quality of scholarship in this domain and reinforce UIN Datokarama Palu's identity as a university committed to a moderate Islamic vision.